Evaluation of the a-amylase enzyme, Carbohydrate Antigen CA-15.3 ( C.A 15.3),and some biochemical variables in the blood serum of breast cancer patients - Nagham abd; Ebtehal Sabri Mohammed; Amer Fadel Dawood (Academic Science Journal)
Evaluation of the amylase enzyme and some biochemical variables in the serum of breast cancer patients for all stages of the disease in patients compared to healthy women.